Faktor-faktor yang Mempengaruhi Pengelolaan Sampah Berbasis Masyarakat di Kelurahan Bantan Kecamatan Siantar Barat Kota Pematangsiantar - Simanungkalit, Chrissanty; Thoha, Achmad Siddik; Charloq, Charloq (Jurnal Serambi Engineering, 2025)
The purpose of this study is to examine the variables that affect the participation of residents of Bantan Village, West Siantar District, Pematangsiantar City in community-based waste management. Cross-sectional study using logistic regression and descriptive analysis is the methodology used. Data were collected through interviews, observations and questionnaires from local communities in the period October to December 2024. Logistic regression analysis uses one independent variable, which is community-based waste management. The independent variables used to find significant factors in community-based waste management are eight variables, namely income (X1), education (X2), knowledge (X3), attitude (X4), facilities and infrastructure (X5), exposure to information media (X6), the role of community leaders (X7), and the availability of waste retribution (X8). The regression model formed from the regression analysis of community-based waste management is LOG (ODDS) =-4.803-5.047X1+2.269X2-0.278X3-4.120X4+3.792X5+4.932X6-3.957X7+3.078X8. Statistically significant factors are income, education, facilities and infrastructure, exposure to information media, and availability of waste collection. The largest factor influencing community-based waste management is exposure to information media, which accounts for more than half of the total influence with a percentage of around 57.6%.